Planning of transit-oriented development cities for greater mobility - Kadar Hamsa, Abdul Azeez; Mustapha, Muslihah (2015)
With the fast growing changes in the economic structure and the need for improved economic growth, it is imperative to indulge in greater mobility of the people for economic benefits. The increasing use of private vehicles in the cities has affected the mobility of people significantly not only during peak hours but also off-peak hours. A number of literatures have stated about negative implications to the cities as a result of the effects on mobility. To improve the mobility of the people, it is very important to provide efficient, attractive and reliable public transportation system to induce a shift from the use of private to public transport. Planning of transit-oriented development (TOD) cities is an important initiative to address the growing needs of urban mobility. Urban mobility can be effectively addressed through the provision of efficient and effective public transportation system. In order to encourage greater use of public transportation system especially rail-based, it is highly necessary to plan the location of rail transit station at areas which could attract the use of rail transit services. It is learned that high density development, mixed land uses and efficient pedestrian infrastructure are the determining components for the surge in the use of public transit system. This paper analyses the land use characteristics of the selected transit stations along one of the existing Light Rail Transit (LRT) system in Kuala Lumpur to understand its possible effects on the passenger ridership.